2023
DOI: 10.1155/2023/7434012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interrow Spacings on Growth, Yield, and Yield Components of Common Bean (Phaseolus vulgaris L.) Varieties in the Central Rift Valley of Ethiopia

Abstract: The common bean is the crop used as food, feed, and to improve soil fertility. However, the production and productivity were affected by poor nutrition and fertilizer management, inappropriate interrow spacings, and the poor genetic makeup of the crops in Ethiopia. Hence, a study was conducted in two research stations at Arsi Negele and Melkasa Agricultural Research Center (MARC), during 2019 cropping season. The treatments consisted of three interrow spacings (30 cm, 40 cm, and 50 cm) and three common bean va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…This result was consistent with the finding of Gupta and Sharma (2000) who reported that nitrogen promoted plant growth and greenness thus slowing the ripening of Onion plants. Moreover, this result is concomitant with finding of Yamasaki and Tanaka (2005) and Nebret (2012) who reported that a high nitrogen application levels are significantly delayed maturity. Early maturation at the control level may be due to insufficient nutrient intake that slows plant growth; thus it entered the fertility phase and matured earlier.…”
Section: Days To 90% Physiological Maturitysupporting
confidence: 86%
“…This result was consistent with the finding of Gupta and Sharma (2000) who reported that nitrogen promoted plant growth and greenness thus slowing the ripening of Onion plants. Moreover, this result is concomitant with finding of Yamasaki and Tanaka (2005) and Nebret (2012) who reported that a high nitrogen application levels are significantly delayed maturity. Early maturation at the control level may be due to insufficient nutrient intake that slows plant growth; thus it entered the fertility phase and matured earlier.…”
Section: Days To 90% Physiological Maturitysupporting
confidence: 86%